2019
DOI: 10.1111/jvim.15474
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium tetrathiomolybdate treatment of copper‐associated hepatopathy in dogs

Abstract: Background Copper‐associated hepatopathy (CAH) is a common cause of liver disease in dogs. Although d ‐penicillamine can be an effective treatment, some dogs fail treatment or develop adverse effects. Ammonium tetrathiomolybdate (TTM) has been used to treat pathologic copper accumulation in other species, but its therapeutic potential for CAH is unknown. Objectives To investigate short‐term safety and efficacy of TTM for treatment of CAH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…with expertise in hepatopathology. The H&E stained slides were scored for necroinflammatory activity and fibrosis as described elsewhere (Langlois et al 2019). Briefly, scores were assigned for the degree of fibrosis (0 to 4), centrilobular inflammation (0 to 3), portal inflammation (0 to 3), lobular necrosis (0 to 2) and piecemeal necrosis (0 to 3).…”
Section: Hepatic Histopathology and Copper Determinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…with expertise in hepatopathology. The H&E stained slides were scored for necroinflammatory activity and fibrosis as described elsewhere (Langlois et al 2019). Briefly, scores were assigned for the degree of fibrosis (0 to 4), centrilobular inflammation (0 to 3), portal inflammation (0 to 3), lobular necrosis (0 to 2) and piecemeal necrosis (0 to 3).…”
Section: Hepatic Histopathology and Copper Determinationsmentioning
confidence: 99%
“…The pathologic hepatic copper accumulation in affected dogs can result in progressive disease and eventually cirrhosis and death if left untreated (Hoffmann et al 2006, Dirksen & Fieten 2017. Copper chelating agents and dietary copper restriction are used to reduce hepatic copper burdens in affected dogs, but treatment responses and treatment duration are variable (Fieten et al 2013a,b, 2014, Langlois et al 2019, Webster et al 2019. Disease management is further complicated by the fact that routine liver enzyme activities are not sensitive markers for hepatitis and do not correlate with hepatic copper concentrations (Fieten et al 2014, Dirksen et al 2017a.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, DPA, due to its metal chelating properties, is used to treat several diseases, including Wilson's disease [10], heavy metal intoxication [11], cystinuria [12], and rheumatoid arthritis [13]; at the same time, DPA's chelating ability is also used in veterinary medicine, and it is used in the treatment of liver disease caused by the accumulation of abnormal storage of copper [14]. In fact, it is considered the initial treatment of choice for most dogs with copper-associated hepatitis, including those with clinical illness and those with moderate to severe hepatic histopathologic abnormalities [15]. Furthermore, this veterinary medicine is also used for the long-term oral treatment of lead, or cadmium, and mercury poisoning, or cysteine urolithiasis [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…[3] The investigations performed in the last five decades by several research groups have revealed the importance of sulfidomolybdates in diverse areas of science like hydrodesulfurization catalysis, bioinorganic chemistry, medicine, organic synthesis, and solid state 33 S NMR spectroscopy. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] As part of a long-standing research activity we have been investigating the synthetic chemistry and structural aspects of the group(VI) metal chalcogenides. Our contributions in this area have resulted in the synthesis, spectral characterization, and structural identification of several tetrasulfidomolybdates [20,21] and the corresponding W analogues, [22][23][24] charge balanced by organic ammonium cations.…”
Section: Introductionmentioning
confidence: 99%